Accounting of installation and use of solar power plants - NOVICHENKO, L.; PODRAN, A. (Scientific Bulletin of the National Academy of Statistics, Accounting and Audit, 2023)
Through the using of solar power plants, a business entity reduces operating costs by using solar electricity for its own needs and generates income by selling this electricity on the market. The construction of solar power plants in Ukraine is an important factor in the development of the national energy market and a tool for integration into the European renewable energy market. The article examines the role and importance of using solar electricity as one of the types of alternative sources of electricity. The authors investigate the peculiarities of accounting for the initial cost of solar power plants depending on the method of its receipt by an enterprise. In particular, the author presents the correspondence of accounting accounts, which are drawn up upon receipt of a solar power plant when it is purchased for cash, in case of its construction by the enterprise using the economic and contractor methods. The procedure for recognition and valuation of solar power plants as an object of fixed assets is substantiated. It is noted that the costs of forming the initial cost of a solar power plant should be accounted for by using the relevant subaccounts of account 15 “Capital Investments”. The article also presents the results of the impact of establishing the useful life and depreciation method of a solar power plant on the financial results before corporate income tax.